PERAN SEKOLAH EKSPOR DALAM MENINGKATKAN PANGSA EKSPOR INDONESIA MELALUI PROGRAM MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) STUDI INDEPENDEN - Wulan, Dewi Antoko (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2024)
This research is a qualitative research method that focuses on the aim of measuring how important the role of the Export School is in increasing the number of exports in Indonesia as measured through an Independent Study on the Merdeka Learning Campus Merdeka (MBKM) 2023 Program. Researchers hope that this research can have benefits in improving students' abilities in the export sector and can inspire innovative ways of learning and training in the academic environment. The Export School has such an important role as a provider of learning platforms for students and people who want to learn about exports. Thus, through this program, researchers hope that many new Indonesian exporters will emerge who are skilled and innovative in the field of exports so that digital businesses can be formed more optimally in accordance with the expectations of the Indonesian Minister of Trade and the Indonesian Minister of Cooperatives and SMEs who have launched the emergence of 500 thousand new exporters in Indonesia in less than 10 years.